Validity of Heat Teaching Material Integrated Joyful Learning to Promote Student’s Creative Thinking Skills - Yasni, Yuli; Asrizal, Asrizal; Amir, Harman; Jonuarti, Riri (Universitas Negeri Padang, 2025)
The development of education in the 21st century demands teachers to innovate by integrating technology into the learning process and fostering students’ creative thinking skills. However, preliminary studies revealed that students’ creative thinking abilities remain low, and the existing teaching materials have not fully supported joyful and engaging learning. This study aims to determine the validity level of a digital learning material on the topic of heat, integrated with the Joyful Learning approach to enhance students’ creative thinking skills in senior high school. The research employed a Research and Development (R&D) method using the Hannafin and Peck model, which consists of three stages: need assess, design, and develop/implement. The research instrument used was a validity questionnaire to assess the feasibility of the developed digital material. The results showed that the digital learning material achieved a validity score of 0.95, categorized as highly valid. Therefore, the developed digital material on heat integrated with Joyful Learning is considered valid and feasible for physics learning to foster students’ creative thinking skills.